2014
DOI: 10.1002/eat.22246
|View full text |Cite
|
Sign up to set email alerts
|

Mandating weekly weight gain in a day treatment program for eating disorders

Abstract: This study demonstrated the benefits of an alteration in protocol that required no additional financial or human resources. Further studies are needed to validate the effectiveness of various day treatment protocol parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…When looking at the 17 studies deemed to have the lowest risk of bias, the pattern of findings is similar to that of the rest of the literature, with 13 of the 17 studies finding evidence to support the effectiveness of treatment to improve motivation to change (Allen et al, ; Cassin et al, ; Geller et al, ; George et al, ; Gowers & Smyth, ; Hillen et al, ; Hötzel et al, ; Kuge et al, ; Leung, Ma, & Russell, , ; McHugh, ; Tchanturia, Larsson, & Brown, ; Touyz et al, ; Wade et al, ). Of the remaining four Wade et al () and Shingleton et al (), as noted previously, presented mixed findings while Thaler et al () and Dingemans et al () found no significant improvements in motivation to change.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…When looking at the 17 studies deemed to have the lowest risk of bias, the pattern of findings is similar to that of the rest of the literature, with 13 of the 17 studies finding evidence to support the effectiveness of treatment to improve motivation to change (Allen et al, ; Cassin et al, ; Geller et al, ; George et al, ; Gowers & Smyth, ; Hillen et al, ; Hötzel et al, ; Kuge et al, ; Leung, Ma, & Russell, , ; McHugh, ; Tchanturia, Larsson, & Brown, ; Touyz et al, ; Wade et al, ). Of the remaining four Wade et al () and Shingleton et al (), as noted previously, presented mixed findings while Thaler et al () and Dingemans et al () found no significant improvements in motivation to change.…”
Section: Resultsmentioning
confidence: 77%
“…Four of the total 42 studies (Ackard et al, ; Dingemans et al, ; Thaler et al, ; Thaler et al, ) found no improvements on any measure of motivation to change. The studies examined diverse treatment programs with no focus on a particular intervention, making it difficult to assess whether it was individual or combined elements of the treatment program that failed to improve motivation to change.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this initial description, many DPs have been established around the world and while adopting a similar approach to that originally described, also report variations in the program such as number of days, number of meals, and addition of individual sessions [4] or use of mandated weight gain required to remain in a program versus recommended weight gain [5]. Published evaluations of changes over admission to discharge show significant increases in weight (for those who are underweight) and significant improvements in psychological functioning.…”
Section: Introductionmentioning
confidence: 99%